Traits to Ecosystems: The Ecological Sustainability Challenge When Developing Future Energy Crops - Weih, Martin; Hoeber, Stefanie; Beyer, Friderike; Fransson, Petra (Frontiers in Energy Research, 2014)
Today, we are undertaking great efforts to improve biomass production and quality traits of energy crops. Major motivation for developing those crops is based on environmental and ecological sustainability considerations, which however often are de-coupled from the trait-based crop improvement programs. It is now time to develop appropriate methods to link crop traits to production system characteristics set by the plant and the biotic communities influencing it; and to the ecosystem processes affecting ecological sustainability. The relevant ecosystem processes involve the net productivity in terms of biomass and energy yields, the depletion of energy-demanding resources (e.g., nitrogen, N), the carbon dynamics in soil and atmosphere, and the resilience and temporal stability of the production system. In a case study, we compared aspects of N use efficiency in various varieties of an annual (spring wheat) and perennial (Salix) energy crop grown under two nutrient regimes in Sweden. For example, we found considerable variation among crops, varieties, and nutrient regimes in the energy yield per plant-internal N (megajoule per gram per year), which would result in different N resource depletion per unit energy produced.